Embryonic Stem Cell-like Population within Venous Malformation Expresses the Renin–Angiotensin System. Issue 4 (April 2019) - Tan, Elysia M.S.; Brasch, Helen D.; Davis, Paul F.; Itinteang, Tinte; Tan, Swee T.
Abstract : Background: We have recently demonstrated the presence of a NANOG + /pSTAT3 + /OCT4 + /SOX2 + /SALL4 + /CD44 + embryonic stem cell (ESC)-like subpopulation localized to the endothelium and a NANOG + /pSTAT3 + /SOX2 + /CD44 + subpopulation outside of the endothelium, within subcutaneous VM (SCVM) and intramuscular VM (IMVM). We have also shown the expression of components of the renin-angiotensin system (RAS): (pro)renin receptor (PRR); angiotensin converting enzyme (ACE), angiotensin II receptor 1 (ATIIR1) and angiotensin II receptor 2 (ATIIR2), in both SCVM and IMVM. This study investigated whether the ESC-like subpopulations within SCVM and IMVM expressed the RAS. Methods: Formalin-fixed paraffin-embedded sections of two representative samples from each of the seven SCVM and seven IMVM patients included in our previous studies underwent dual immunofluorescence (IF) immunohistochemical (IHC) staining for ESC marker OCT4 or SOX2 with PRR, ACE, ATIIR1, and ATIIR2. Results: IF IHC staining demonstrated the expression PRR by the OCT4 + cells on the endothelium and outside the endothelium in SCVM and IMVM. ACE was expressed by the SOX2 + cells, predominantly in the endothelium in SCVM and IMVM. ATIIR1 was expressed by the SOX2 + cells on the endothelium and outside the endothelium in SCVM and IMVM. ATIIR2 was expressed by the OCT4 + endothelium and outside the endothelium in SCVM and IMVM. Conclusions: Components of the RAS are expressed by ESC-like subpopulations within both SCVM and IMVM. These primitive subpopulations may be a novel therapeutic target by manipulation of the RAS using existing medications. Abstract : Supplemental Digital Content is available in the text.